The British Library Newspaper Collection: Long Term Storage, Preservation and Access - Fleming, Patrick; Spence, Phil (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
The British Library has recently unveiled plans for improving the collection care of, and digital access to, one of the world’s greatest newspaper collections. The collection, which dates from the 16th century, contains UK titles as well as 200 overseas titles and is at risk. 15% of the collection is unusable because of its deterioration, and there are pressures on space and a need to develop greater digital content for access. The solution is to place all of the physical newspapers into a new, state of the art Newspaper Storage Building at Boston Spa, the British Library’s main storage and logistics site, and home to its document delivery service. The building will comprise of 160 km of high density shelf space, fully automated under special environmental conditions including low oxygen, regulated 16 degree Celsius temperature, and 52% humidity. Future access to the collection will be at the BL’s main Library site at St Pancras, in a specially equipped reading room, so that researchers can integrate other collection items into their studies. However, access will be by surrogate means, initially microfilm, stored in London, and then, increasingly, digital access. By March 2009, the British Library will have digitised 3 million historic newspapers with JISC funds, and this content will be available to readers for free in reading rooms and on a paid for basis online, or via subscriptions. The Library is investigating a similar model going forward with a private sector partner who is willing to digitise and sell online out of copyright newspapers from the BL’s collection for a fixed period. This will provide digital content for customers in reading rooms, free at the point of access.